Monetary policy and bank-type resilience in Germany from 1999 to 2022 - Tim Florian Sepp; Karl-Friedrich Israel; Benjamin Treitz; Tom Hartl (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2024)
This paper examines the heterogeneous effects of the ECB's monetary policies on the resilience of the German banking system between 1999 to 2022. We distinguish between the main bank types in Germany: Large Banks, Regional Banks, Sparkassen, Landesbanken and Credit Unions. We proxy bank-type resilience by a zscore measure. We use structural monetary policy shocks relying on high-frequency identification methods. Unconventional monetary policy shocks are decomposed into three parts: timing shocks, forward guidance, and quantitative easing. We estimate the resilience of German bank types in response to expansionary monetary policy shocks by producing impulse response functions through local projections. Conventional monetary easing is associated with weakened resilience for all bank types. Unconventional monetary policies have heterogeneous effects on German bank types. Shocks to short-term interest rate expectations (i.e. timing shocks) are associated with increasing resilience of Large Banks, Regional Banks and Landesbanken, but with decreasing resilience of the others. Forward guidance only has a positive impact on the resilience of Sparkassen. Large-scale asset purchases through quantitative easing tend to the increase resilience of Large Banks and Sparkassen, but decrease the resilience of Regional Banks, Credit Unions and Landesbanken, in both, the short and long run.
Keywords: E42; E52; G21; M41; 330; Resilience; Financial Stability; Monetary Policy; Unconventional Monetary Policy; Banking System; Germany